Music: Teaching and practice mediated by digital technologies in the 21st century - Amato, Daniel Chris; Hiraga, Cynthia Yukiko (Revista Hipótese, 2022)
Music is present in all human cultures and accentuates its presence when mediated by Digital Technologies in the 21st century. This dossier reflects on the relationship between education, music, and digital technologies and presents experiences in different situations, including the time of the Covid-19 pandemic. This dossier consists of twelve articles and includes a review with transversal content to the theme. It is hoped the reading this work can stimulate future research on this relationship.
Keywords: Music; Education; Digital technologies